Preventive small-quantity lipid-based nutrient supplements reduce severe wasting and severe stunting among young children: An individual participant data meta-analysis of randomized controlled trials - Dewey, Kathryn G.; Ashorn, Per; Ruel, Marie T.; Leroy, Jef L.; Huybregts, Lieven; Becquey, Elodie (Elsevier, 2022)
Background: Meta-analyses show that small-quantity lipid-based nutrient supplements (SQ-LNS) reduce child wasting and stunting. There is little information regarding effects on severe wasting or stunting. Objective: We aimed to identify the effect of SQ-LNS on prevalence of severe wasting (weight-for-length z-score < -3) and severe stunting (length-for-age z-score < -3). Methods: We conducted a two-stage meta-analysis of individual participant data from 14 randomized controlled trials of SQ-LNS provided to children 6 to 24 mo of age. We generated study-specific and subgroup estimates of SQ-LNS vs. control and pooled the estimates using fixed-effects models. We used random effects meta-regression to examine study-level effect modifiers. In sensitivity analyses, we examined whether results differed depending on study arm inclusion criteria and types of comparisons.